Violence suffered by women supporters of bleachers (Research, Society and Development, 2021)
This scientific article aims to detect, understand and discuss the violence that women fans of the stands suffer in soccer stadiums. The methodology used in the construction of this study was bibliographic research, with investigation of the subject in electronic newspapers and magazines, books, scientific articles and sports articles on football websites and blogs. The results obtained showed that the interest of women in soccer has gradually increased and that the number of fans who attend bleachers has kept up with the growth. However, the referred sport remains an environment steeped in masculinity and stereotyping of women, which results in their failure to approach or even withdraw from the games of the teams at heart. It was concluded that there is an urgent need for unity among the agents involved in the organization of matches, namely, Football Clubs, Organized Supporters, Football Federations, Public Security Departments, Military Police, Public Prosecutor's Office and Confederation in the construction, participation and encouragement of creation of permanent, preventive and educational campaigns to combat machismo, harassment and other violence experienced by women in the stadiums, all this coupled with concrete and swift attitudes of applicability of existing legal measures, with a view to making punishment effective, in the form of the law, of the aggressors.